RESIDU INSEKTISIDA SIDAZINON PADA KACANG PANJANG (VIGNA SINENSIS) YANG DIHASILKAN DI DESA TUNJUK SELATAN, KECAMATAN TABANAN, KABUPATEN TABANAN - Ayu Lani Triani, I Gusti (Bumi Lestari; Vol 7 No 1, 2012)
Research was conducted in long bean (Vigna sinensis) that has been produced in Tabanan district, Tabanan Regency concerning the residue of Sidazinon insecticide. The aims of this study are to : know dosage Sidazinon insecticide utilized by farmer in Tabanan district and the level of the residue of Sidazinon insecticide found in long bean. The determination of the sample of the farmer of long bean was done in proportional and purposive sampling. The sample was taken in Tabanan district, in Tabanan Regency. For the selection of village, search by 10 % from amount village exist, so five of the farmer of long bean were obtained in Tabanan district. The finding show that the residue of the Sidazinon insecticide in long bean produced in Tabanan district in influenced by the use of dosage was 9,275 ml/ are. The residue of Sidazinon insecticide in long bean averagely produced in Tabanan district was 0,03045 ppm.
Keywords: residu, insektisida, Sidazinon